ANALISIS ALGORITMA ROUND ROBIN, LEAST CONNECTION, DAN RATIO PADA LOAD BALANCING MENGGUNAKAN OPNET MODELER - Husain Nasser; Timotius Witono (Jurnal Informatika, 2016)
Load balancing is a technique to distribute traffic load into two or more lanes to reach balanced connection, optimized traffic performance, maximized data throughput, minimized delay, and avoiding data overload. Load balancing in a computer network used to modulate the balance of bandwidth usage between multiple internet service provider. This research contains Load Balancing performance test on HTTP, FTP, and VoIP. Testing application used is OPNET Modeler 14.5 simulator, and load balancing algorithm which being tested is Least Connection, Round Robin, and Ratio. The test results shows generally Ratio is better than Least Connection and Round Robin. Ratio excels on handling End-to-End Delay and Jitter in VoIP,  while Least Conncetion shows the highest throughput value in all test cases.